The impact of intraoperative prone lumbar fluoroscopy under anesthesia on the selection of lowest instrumented vertebra and surgical outcomes in adolescent idiopathic scoliosis with lumbar structural curves - Lang Mai; Yankui Liu; Ruijue Zhu; Pan Zhou; Jiawei Di; Junlin Yang; Zifang Huang; Lei He (BMC Musculoskeletal Disorders)
Abstract Purpose To explore the role of intraoperative prone lumbar fluoroscopy under anesthesia in guiding lowest instrumented vertebra (LIV) selection in adolescent idiopathic scoliosis (AIS) patients with lumbar structural curves and its subsequent impact on surgical outcomes.pap. Methods This retrospective cohort study included 45 AIS patients with lumbar structural curves who underwent posterior spinal deformity correction surgery at the Scoliosis Center, the Third Affiliated Hospital of Sun Yat-sen University between 2020 and 2022.The reduced group refers to the choice of a more superior LIV based on intraoperative lumbar fluoroscopy in the prone position, resulting in fewer fused levels than the preoperative plan, while the non-reduced group leaves the preoperative plan unchanged.We analyzed the demographic information, radiographic data, surgical parameters (including curve correction rates, coronal and sagittal balance, and LIV-related parameters), and complication rates, with statistical significance set at p < 0.05. Results In the reduced group, 57.8% of patients had a reduced number of fused levels. When compared to the non-reduced group, there were no significant differences in the major curve correction rate (the reduced group: 77.6%, the non-reduced group: 71.7%, p = 0.95), coronal balance at final follow-up (p = 0.97), or sagittal balance at final follow-up (p = 0.64), with at least 2 years of follow-up (average 33.3 ± 15.6 months). Postoperative LIV-related parameters, including tilt angle, rotation, and the distance from the center sacral vertical line (CSVL), showed no significant differences between the two groups (p > 0.05). All patients achieved satisfactory postoperative correction, with no adverse events or revision surgeries required due to distal junctional issues. Conclusion Intraoperative prone lumbar fluoroscopy under anesthesia provides precise guidance for LIV selection, reducing the number of fused levels without compromising curve correction or overall spinal balance. This technique is both safe and effective, helping to optimize AIS surgical outcomes while preserving lumbar mobility. Further multicenter studies are needed to validate these findings and assess their long-term functional impact.